Sabhara Four-Wheel Patrol Management in Preventing Criminal Acts of Theft of Two-Wheeled Motorized Vehicles in the Jurisdiction of Jatinangor Police - Januar, Adrian Vico (Police Studies Review, 2024)
West Java Province ranks sixth with a total crime of 4.481 in Indonesia after the Central Sulawesi Province Police Headquarters (adapted in BPS Statistics of Criminal Statistics 2019). Based on data obtained from Sumedang District Basic Intel in 2019, Jatinangor is a crime-prone region. The majority of crime is theft, with the mode of operation which is motor vehicle theft. The problem that arose in the Jatinangor area attracted researchers to find out how the police action to deal with curanmor with the Sabhara Unit conducted a patrol to suppress the amount of curanmor that occurred. Organizational management of the Patrol Unit is needed to achieve the goal of reducing the amount of compensation. The implementation of the main tasks owned by the Patrol Unit listed in Article 23 of the National Police Office No. 1 of 2017 will be analyzed using management theory from George R. Terry. This study uses a qualitative approach and field research methods. This research is a qualitative research using interview, observation, and document inspection methods. Data analysis was performed by data reduction, data presentation, and drawing conclusions. The results of this study indicate that prevention efforts by four-wheeled Sabhara patrols have not had a significant impact on reducing the number of criminal acts of curanmor in the Jatinangor police station. This study also found that there are factors that influence the sabhara four-wheeled patrol, namely, supporting factors such as adequate facilities and infrastructure, adequate patrol budget, and inhibiting factors such as, the role of the community that is still apathetic, patrol targets where patrol cars cannot entering a narrow lane / alley, and inadequate personnel.